2019
DOI: 10.1016/j.jtho.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Capture–Based Genomic Profiling of Circulating Tumor DNA from Patients with Advanced Non–Small Cell Lung Cancer

Abstract: Introduction: Genomic profiling informs selection of matched targeted therapies as part of routine clinical care in NSCLC. Tissue biopsy is the criterion standard; however, genomic profiling of blood-derived circulating tumor DNA (ctDNA) has emerged as a minimally invasive alternative. Methods: Hybrid capture-based genomic profiling of 62 genes was performed on blood-based ctDNA from 1552 patients with NSCLC. Results: Evidence of ctDNA was detected in 80% of samples, and in 86% of these cases, at least one rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…MSAF is a valid tool for quantifying the tumor fraction of cell free DNA [16–18]. Numerous studies have shown that the MSAF, or baseline ctDNA level, is a prognostic factor in patients receiving chemotherapy [25], targeted therapy [26,27], and immunotherapy [21, 28–30], although most of the prognostic value of MSAF is correlated with baseline tumor burdens in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSAF is a valid tool for quantifying the tumor fraction of cell free DNA [16–18]. Numerous studies have shown that the MSAF, or baseline ctDNA level, is a prognostic factor in patients receiving chemotherapy [25], targeted therapy [26,27], and immunotherapy [21, 28–30], although most of the prognostic value of MSAF is correlated with baseline tumor burdens in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor DNA (ctDNA) is shed from tumor cells throughout the body. The maximum AF among all somatic mutations detected in plasma sample can provide an estimate of the ctDNA fraction in blood [16–18]. This may be based on the hypothesis that mutation with maximum AF in blood is shared by the most malignant cells and represents the largest clone in a given patient's tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive assessment of ctDNA from 1552 NSCLC patients, using hybrid capture-based genomic profiling, MET exon 14 skipping mutations were detected in 1.9% of cases. Moreover, additional activating SNVs of MET (p. L1195V, p. D1228H, and p. Y1230C) could be detected in three cases [ 50 ].…”
Section: Available Assays and Target Genomic Alterations In Lung Cmentioning
confidence: 99%
“…The maximum somatic allele frequency (MSAF) is a useful bioinformatics tool for estimating the amount of tumor fraction of cell-free DNA in peripheral blood samples (10). Previous studies have revealed that a lower MSAF level was associated with a higher risk of missing important genomic alterations in the plasma, such as EGFR exon 19 deletion and EGFR T790M that are predictive of response to EGFR tyrosine kinases in advanced NSCLC (10,11). However, there exist limited data regarding the association between MSAF and treatment outcomes from ICIs.…”
Section: Introductionmentioning
confidence: 99%